Fishing Gears and Practices in the Aquatic Systems of Kanchanpur District, Nepal: Issue and Trends - Joshi, Yagya Raj (Journal of Institute of Science and Technology, 2025)
Various types of fishing gears and fish catching methods have been used worldwide for harvesting fishes from natural water bodies since antiquity. The present work aims to elucidate the current fishing gears and practices and knowledge of indigenous people and others about the impact of overfishing on wild fisheries in the aquatic systems of Kanchanpur district, Nepal. Data and information on fishing gears, fishing methods and knowledge about the impact of overfishing were obtained through direct observation and interactions with the local fishers of all the municipalities and rural municipalities of the Kanchanpur district through structured questionnaires; annual reports and programs of governmental and non-governmental organizations from October 2022 to September 2023. Fifteen types of conventional fishing gears, four types of unconventional fishing practices and nine fishing techniques viz., netting, trapping, hand lining and long lining, fish barrier, dewatering and hand gathering, spearfishing, poisoning, electrofishing and blast fishing were found to be followed by the fishers in different seasons. Traditional fishing practices were used by 53% fishers while massive destructive fishing practices by remaining ones (47%). Statistically, there was significant difference in the use of fishing gears and devices by the fishers (p < 0.05). All the fishers were unaware about the impact of overfishing of wild fish resources. Use of indiscriminate massive destructive fishing techniques and small mesh sized nets, fish capturing during breeding seasons and lack of awareness on proper scientific fishing methods are the main challenges for the conservation of feral fishes in the aquatic bodies of district.